The Synergistic Effect of a Bimetallic Catalyst for the Synthesis of Carbon Nanotube Aerogels and their Predominant Chirality - Moon, Sook Young; Kim, Woo Sik (WILEY-V C H VERLAG GMBH, 2019)
Synthesis of continuous spinnable carbon nanotube (CNT) fibers is the most promising method for producing CNT fibers for commercial applications. The floating-catalyst chemical vapor deposition (FC-CVD) method is a rapid process that achieves catalyst formation, CNT nucleation and growth, and aerogel-like sock formation within a few seconds. However, the formation mechanism is unknown. Herein, the progress of CNT fiber formation with bimetallic catalysts was studied, and the effect of catalyst composition to CNT fiber synthesis and their structural properties was investigated. In the case of bimetallic catalysts, the carbon source rapidly decomposes and generates various secondary hydrocarbon species, such as CH4, C2H4, C2H2, C3H6, and C4H10 whereas monometallic catalysts generate only CH4 and C2H4 on decomposition. CNT fiber formation with Fe1Ni0 begins about 400 mm from the reactor entrance, whereas CNT formation with Fe0.8Ni0.2 and Fe0.5Ni0.5 begins at about 500 and 300 mm, respectively. The formed CNT bundles and individual CNTs are oriented along the gas flow at these locations. The enhanced rate of fiber formation and lowering of growth temperature associated with bimetallic catalysts is explained by the synergistic effects between the two metals. The synthesized CNTs become predominantly semiconducting with increasing Ni contents.
Keywords: FIBERS; GROWTH